1970
DOI: 10.1085/jgp.56.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Specific Uncoupling of Excitation and Contraction in Mammalian Cardiac Tissue by Lanthanum

Abstract: Arterially cannulated rabbit interventricular septal tissue was exposed to 5-40 /kM La in 2.5 mM Ca perfusate. Immediately following perfusion with La two concurrent events were consistently observed: (a) a rapid decline of active tension to a lesser steady-state value, and (b) an abrupt, release of short duration of tissue-bound Ca. The magnitude of both events was directly related to the [La]o. If the duration of exposure to La was brief, contractility returned toward normal upon return to the La-free perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…The increased duration of the Purkinje cell action potential found by us confirms similar findings reported by Sanborn and Langer (20) in rabbit ventricular cardiac cells . These authors reported the displacement by lanthanum of calcium bound superficially, probably to the sarcolemma (20) . In view of these results, the possibility exists that the regions where selective deposition of lanthanum was observed in the present study could represent the sites where contractile dependent calcium is normally bound .…”
Section: Ultrastructural Localization Of Lanthanum Depositsmentioning
confidence: 97%
“…The increased duration of the Purkinje cell action potential found by us confirms similar findings reported by Sanborn and Langer (20) in rabbit ventricular cardiac cells . These authors reported the displacement by lanthanum of calcium bound superficially, probably to the sarcolemma (20) . In view of these results, the possibility exists that the regions where selective deposition of lanthanum was observed in the present study could represent the sites where contractile dependent calcium is normally bound .…”
Section: Ultrastructural Localization Of Lanthanum Depositsmentioning
confidence: 97%
“…It is generally supposed that a primary and essential step for the influx of Ca2+ is the binding to surface membranes in barnacle muscle (HAGIWARA and TAKA-HASHI, 1967), mammalian myocardial tissues (SANBORN and LANGER, 1970) and isolated skeletal sarcoplasmic reticulum (CHEVALLIER and BUTOW,1971 tonic component was more marked than that of phasic one.…”
mentioning
confidence: 99%
“…On the other hand, La3+ equally suppressed the actions of HL-A, isoprenaline and ouabain. This is reasonable because La3' decreases any Ca movement across the membrane (Sanborn & Langer, 1970;Langer & Frank, 1972;Reeves & Sutko, 1979;Burt & Langer, 1982). Second, both HL-A and isoprenaline augmented the contraction of partially depolarized muscles depending on the external Ca concentration while ouabain failed to do so.…”
Section: Discussionmentioning
confidence: 91%